Perilaku Pengambilan Keputusan pada Future Accountant - Kusuma, Gabriella; Wany, Eva; Prayitno, Budi (Ekomania, 2024)
This research examines the influence of mental health on future accountants in decision-making behavior through professional ethics, conflicts of interest and the organizational environment. By distributing online questionnaires to 41 respondents who are accounting students as future accountants, the results of this research show that Professional Ethics and Organizational Environment have a significant influence on Decision Making. The benefit of this research is that the wider community can understand the importance of future accountants' mental health in decision making because accountants who have good mental health tend to make better decisions.